The feasibility of using ultrasound during follow-up for superficial non-melanoma skin cancers after electronic brachytherapy - Goyal, Uma; Suszko, Justin; Stea, Baldassarre (Journal of Contemporary Brachytherapy, 2017)
Purpose : Non-melanoma skin cancers (NMSCs) can be treated with a number of modalities including surgery, topical chemotherapy, or radiotherapy. Amongst the radiotherapeutic options, electronic brachytherapy (eBT) is an appealing treatment as it is usually given in a few fractions, it leads to good outcomes, and is increasingly being used. However, currently no follow-up imaging is routinely used or recommended to evaluate treatment response of NMSC. We aimed to use ultrasound (US) in follow-up after eBT for superficial NMSC to assess its feasibility in detecting possible tumor response. Material and methods : Fourteen patients were treated between 2013-2015 for a NMSC using eBT. US guidance was used for treatment planning prior to eBT initiation. After completion of eBT, patients were seen in follow-up for both clinical exam and a repeat US at 1 month to evaluate if tumor response was detectable. Results : Of the 14 patients, 6 were male and 8 were female. The mean age was 71 years. With a median follow-up of 20.5 months, all patients had a complete response based on physical exam. Eleven patients appeared to have a complete response based on US obtained > 1 month after completing eBT. To date, there have been no local recurrences or progression, and all patients are alive. Conclusions : US is an objective imaging modality that may be able to assess NMSC response after eBT. Based on follow-up imaging, further treatment or observation may be recommended. Although this study is hypothesis generating, larger studies with pathologic confirmation of recurrences would be needed to validate US use for follow-up, avoiding possible painful and scarring biopsies in case of low suspicion of recurrence.